PENGARUH BAURAN PEMASARAN PERGURUAN TINGGI TERHADAP KEPUASAN DAN DAMPAKNYA KEPADA LOYALITAS MAHASISWA PADA TIGA PTS TERKEMUKA DI KOTA BANDUNG - Elisabeth Koes Soedijati (Center for Economic Studies Universitas Katolik Parahyangan, 2009)
The aim of this study is to obtain the description of the impact of the marketing mix towards the satisfaction and loyalty of students of the three distinguished universities in Bandung. It deals with variables of: (1) marketing mix of higher education, (2) students satisfaction, (3) the loyalty of students. This research employed the survey method with quantitative approach. From the total population of 1753 students, 95 participated in the survey and they comparised of students majoring in accounting, class 2007/2008 in the bachelor’s degree program in-the faculty of economics. The results showed that the seven sub-variables of marketing mix would have impacts on the student satisfaction, even though only six of them showed significance. The order of the sub-variables with significant effect based on the student satisfaction is: (1) the product/ service of the schools with ρyx1 = 0,5152; (2) service price of the school with ρyx2 = 0,2222; (3) school location with ρyx3= 0,2152; (4) the process/ management of school service with ρyx4 = 0.2132 ; (5) physical evidence of facilities and infrastructure with ρyx6 = 0.1732 ; (6) human resources with ρyx5 = 0,1592. The accumulative amount of the impact of those variables towards student satisfaction is 97%, while the last 3% is the effects of other factors out of the scope of this study. School promotion would also effect student satisfaction, yet it was insignificant. Student satisfaction would lead significantly towards their loyalty with ρzy = 0,8452 = 71,40%, while the last 28,60% is the impact caused by other factors not in the scope of this study.